Instruments for the identification of patients in need of palliative care: protocol for a systematic review of measurement properties. Issue 5 (May 2020) - Teike Lüthi, Fabienne; Mabire, Cédric; Rosselet Amoussou, Joëlle; Bernard, Mathieu; Borasio, Gian Domenico; Ramelet, Anne-Sylvie
ABSTRACT: Objective: The objective of this review is to provide a comprehensive overview of the psychometric properties of available clinician-reported instruments developed to identify patients in need of general and specialized palliative care in acute care settings. Introduction: Identification of patients in need of palliative care has been recognized as an area where many health care professionals need guidance. Differentiating between patients who require general palliative care and patients with more complex conditions who need specialized palliative care is particularly challenging. To our knowledge, no dedicated instruments are available to date to assist health care professionals to make this identification. Inclusion criteria: Included studies will report on i) instruments aiming to identify patients in need of palliative care, ii) adult patients in need of palliative care in acute-care settings, iii) clinician-reported outcome measures, or iv) the development process or one or more of its measurement properties. Studies conducted in intensive care units, emergency departments, or nursing homes will be excluded. Methods: We will search for studies published in English and French in a variety of sources, including Embase, Medline Ovid SP, PubMed, CINAHL EBSCO, Google Scholar, government websites, and hospice websites. All citations will be screened and selected by two independent reviewers. Data extraction, quality assessment, and syntheses of included studies will be performed according to the COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) criteria. Systematic review registration number: PROSPERO CRD42020150074.